2009
DOI: 10.1055/s-2008-1039060
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Apoptosis by Fas/FasL: Harmful or Advantageous in Cardiac Surgery?

Abstract: Polymorphonuclear leukocytes or neutrophils are the main executors of cellular death, both in septic inflammation during bacterial infection and in sterile inflammation during trauma or surgery. Whereas in septic inflammation neutrophils perform a useful function to fortify the host's defense against infection, in sterile inflammation, by contrast, they contribute to unwelcome tissue damage. Regardless of the situation, activated neutrophils exhibit a prolonged lifespan and delayed apoptotic death which, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Conversely, augmentation of neutrophil apoptosis accelerates resolution of inflammation. We found that the expression of the pro-apoptotic membrane molecule Apo/Fas (CD95) on granulocytes was significantly increased late in the postoperative period on the 3 rd and 7 th postoperative days in patients with standard cardiopulmonary bypass 21 . In this regard, the significantly increased expression of CD200R on granulocytes, which was found immediately after surgery in the OP group, seems to be a very early endogenous protective mechanism that may intervene in order to dampen the exaggerated inflammatory response due to cardiac surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Conversely, augmentation of neutrophil apoptosis accelerates resolution of inflammation. We found that the expression of the pro-apoptotic membrane molecule Apo/Fas (CD95) on granulocytes was significantly increased late in the postoperative period on the 3 rd and 7 th postoperative days in patients with standard cardiopulmonary bypass 21 . In this regard, the significantly increased expression of CD200R on granulocytes, which was found immediately after surgery in the OP group, seems to be a very early endogenous protective mechanism that may intervene in order to dampen the exaggerated inflammatory response due to cardiac surgery.…”
Section: Discussionmentioning
confidence: 94%
“…In line with the first proposed mechanism, we showed that B. abortus infection can induce apoptosis of primary mouse osteoblasts. Whether pathogen-induced apoptosis is harmful or beneficial to the host has been a considerable source of debate (26,56). Osteoblast apoptosis may be responsible, at least in part, for the damage produced by Brucella infection to bone since apoptosis would reduce the number of osteoblasts in bone.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiosurgical procedures are inseparately associated with systemic inflammatory response, predominantly when patients have undergone surgery under extracorporeal circulation. That may lead to postoperative complications such as acute lung injury, cardiac low output syndrome, and in extreme cases to multi-organ failure [7,8] Here, TLR receptors play a major role. It has previously been shown that a close link exists between inflammation and apoptosis in atherosclerotic plaques, and our data support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…TLRs are highly conserved genes which mediate the production of cytokines necessary for the development of effective immunity. This gene is expressed most abundantly in peripheral blood leukocytes, and mediates host response to Gram-positive bacteria and yeast via stimulation of NF-jB [7,8].…”
Section: Toll-like Receptor 2 (Tlr2)mentioning
confidence: 99%